A Study of the Problems Related to the Testing of Smoke Emission From Diesel Powered Vehicles in Malaysia - Yaziz, Mohammad Ismail; K., Rravinder (1986)
This study was carried out to examine the smoke emission level from diesel powered vehicles plying Malaysian roads and the problems related to the enforcement of the Motor Vehicles (Smoke and Gas Emission) Rules 1977. The results show that approximately 35% of the lorries examined had excessive smoke emission compared to 33% for taxis, 16% for buses and mini buses, and 13% for cars. Further examination£on of the data did not show any relationship between the degree of smoke emission and parameters such as age and maintainance of the vehicle, or duration since the last mandatory inspect£on by the RTD. A study of the past records of enforcement carnage out by the DOE showed that an average of only 52. 7% of the planned exercises were actually carnage out during 1979 to 1983. This was due to various reasons including manpower and budget problems, equipment, transportation, and weather. The selection of suitable sites for curb-side enforcement is nearly always hampered by the need to select locations which would not cause severe traffic problems and hence did not necessarily match the traffic flow. The main problem faced by the RTD is the lack of space to carry out inspection of the motor vehicles. The results also give a strong indication that some drivers of diesel vehicle may adopt underhand tactics such as tempenng with the engine parts or adding volatile additives into the fuel tanks to achieve short term reductions for smoke emission during the RTD tests.